Performance in Boko Haram’s Religious Fanaticism - Cole, Soji (The journal of religion & society, 2021)
The activities of Boko Haram in Nigeria evolved within a very short time from a religious sect professing hatred for western values, into a violent dissident group. The group has become a threat to the social and political stability of Nigeria and neighboring countries, and they are believed to have links with ISIS and Al-Qaeda. The group’s media-attention strategy includes recording vicious moments of slaughtering captives, displaying victims’ mangled corpses, and sending threatening media messages. Though seen as a propaganda strategy by the group, this paper contextualizes the group’s activities as an extreme and sadistic form of public performances—an otherwise descriptive strategy for complex fanaticism. This article explores a historiographic and analytic description of performance and fanaticism, and underlies the relationship between the two terms as tangible sociological constructs that serve the terror group as mechanism of representation and communication. By applying the frameworks of historical and performance theories, the article describes how the concept of fanaticism shapes and constructs the identity and public actions of Boko Haram.